When do leaves commit to their phenotypic fate? Developmental point of no return on the early leaves from the det2-1 mutant of Arabidopsis thaliana (2025)
The Arabidopsis thaliana det2-1 mutant is widely studied due to its characteristic dwarf phenotype, which arises from its inability to efficiently synthesize brassinosteroids. This deficiency results in distinct leaf morphology compared to the wild-type Columbia (Col-0) plants. Notably, the det2-1 phenotype can be rescued by the addition of exogenous brassinosteroids. The ability to rescue det2-1 plants provides a valuable model for investigating the developmental timepoints at which plants commit to a specific phenotype. By identifying these developmental "points of no return," we can determine when the effect of specific phytohormones, such as brassinosteroids, can influence leaf morphology. This study identified two distinct developmental points of no return during the early development of det2-1 plants by characterizing leaf morphologies and assessing the capacity of det2-1 to rescue its phenotype at specific timepoints. These findings form the basis for future live imaging of det2-1 plants to pinpoint the exact timepoints at which leaves commit to their final shape. Furthermore, this approach will facilitate analysis of cellular growth dynamics to understand how developmental changes contribute to the expressed phenotype.